A polyester-based silica aerogel fiber and a method for preparing the same
Patent Information
- Application Number
- CN202610710665.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-22
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-05-22
AI Technical Summary
但气凝胶骨架脆弱,在传统功能母粒制备的螺杆强剪切及聚酯熔融纺丝的高压高剪切条件下,极易发生破碎、孔隙坍塌,导致隔热功能大幅衰减,如何在纺丝过程中保留气凝胶骨架完整性,成为另一项重要技术难题
(1)本发明所述的制备方法以低特性粘度膜源再生聚酯作为气凝胶载体,于其熔融状态下借助聚二甲基硅氧烷的界面浸润特性,在二氧化硅气凝胶表面形成柔性包覆层,实现气凝胶表面被聚二甲基硅氧烷包覆,隔绝聚酯熔体与气凝胶孔隙直接接触,防止孔隙堵塞;再采用含硅氧烷的扩链剂对低粘度组分进行原位扩链增粘,提升熔体强度;最后将改性后的低粘度组分侧向喂入高特性粘度膜源再生聚酯熔体中,通过分子链拓扑缠结进一步提升丝条熔体强度、改善成丝稳定性,该工艺可避免传统母粒纺丝加工中二次加热与强剪切对气凝胶骨架的破坏。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of functional fiber technology, and particularly relates to a polyester-based silica aerogel fiber and its preparation method. Background Technology
[0002] With increasing environmental awareness and growing demand for resource recycling, the development and application of recycled polyester fibers are receiving increasing attention. Membrane-derived polyester (such as biaxially oriented polyester film scraps and waste packaging film) is an important source of recycled polyester. During the recycling process, it undergoes multiple thermal histories, resulting in a significant reduction in molecular weight. Its intrinsic viscosity is typically only 0.35 dL / g-0.55 dL / g, far below the standard of 0.65 dL / g-0.75 dL / g for conventional spinning-grade polyester. This low molecular weight leads to insufficient melt strength, causing problems such as fuzzing and breakage during spinning, and making winding difficult. This has become a core bottleneck restricting the high-value utilization of membrane-derived polyester.
[0003] Currently, the industry commonly uses a high proportion of blended virgin or bottle-grade polyester to improve the spinnability of membrane-derived polyester. However, this method dilutes the proportion of low-cost recycled materials, significantly reducing product economics. Therefore, effectively improving the melt strength of low-molecular-weight membrane-derived polyester while ensuring a high recycling rate has become the primary challenge for achieving its recycling.
[0004] Meanwhile, the end-use applications of recycled polyester fibers are shifting from ordinary fillers to functional differentiation, with warmth retention being one of the most readily implementable upgrade directions. Traditional fibers often increase the static air content through hollow or crimped structural designs to improve warmth retention. To further reduce the fiber's thermal conductivity, a functional medium with even lower thermal conductivity needs to be introduced. Silica aerogel, with its three-dimensional nanoporous network, boasts a static thermal conductivity as low as 0.012 W / (m·K)-0.015 W / (m·K), earning it the title of "solid air" and making it an ideal lightweight thermal insulation filler. However, the aerogel skeleton is fragile. Under the high-shear conditions of screw spinning in traditional functional masterbatch preparation and the high-pressure, high-shear conditions of polyester melt spinning, it is prone to breakage and pore collapse, leading to a significant reduction in thermal insulation performance. How to maintain the integrity of the aerogel skeleton during the spinning process has become another important technical challenge.
[0005] In summary, developing a new fiber forming system that balances melt strength enhancement with the preservation of aerogel skeleton structure is the only way to overcome the dilemma of utilizing low-value membrane-source polyester and promote its transformation into high-value thermal insulation fiber. Summary of the Invention
[0006] To address the aforementioned technical problems, this invention provides a polyester-based silica aerogel fiber and its preparation method. Using membrane-derived recycled polyester as raw material, a synergistic process of organosilicon coating at the aerogel interface, in-situ chain extension and thickening, and side-feeding blending and homogenization spinning is employed. This process significantly improves the melt strength and spinnability of low-viscosity recycled polyester while retaining the porous thermal insulation skeleton of silica aerogel, ultimately producing a polyester-based silica aerogel fiber with excellent mechanical properties and outstanding thermal insulation effect.
[0007] The first objective of this invention is to provide a method for preparing polyester-based silica aerogel fibers, comprising the following steps: S1. Under the shearing action of a twin-screw extruder, polydimethylsiloxane and silica aerogel are added sequentially to the molten first membrane source recycled polyester and mixed evenly to obtain a pre-dispersed melt. S2. Add a chain extender to the pre-dispersed melt described in S1 and react to obtain a modified melt; S3. Add the modified melt described in S2 to the molten second membrane source recycled polyester, homogenize it, and then spin it to obtain the polyester-based silica aerogel fiber.
[0008] In one embodiment of the present invention, in S1, the intrinsic viscosity of the first membrane-source recycled polyester is 0.30 dL / g-0.40 dL / g, and its chemical structure is polyethylene terephthalate. This intrinsic viscosity range provides moderate melt flow and low shear viscosity, which facilitates the uniform dispersion of high-proportion silica aerogel under low shear conditions and ensures that polydimethylsiloxane fully impregnates and coats the aerogel. When the viscosity is below 0.30 dL / g, the melt strength is insufficient and cannot support a high proportion of aerogel, making it prone to agglomeration or system collapse. When the viscosity is above 0.40 dL / g, the melt viscosity increases and the dispersion resistance increases, which can cause the aerogel to undergo skeleton breakage and pore collapse under strong shear. And / or, the temperature of the molten first membrane-source recycled polyester is 245℃-265℃; this temperature range matches the low viscosity characteristics of the first membrane-source recycled polyester; the lower limit of 245℃ ensures that the low molecular weight polyester melts fully, giving the melt sufficient fluidity to achieve low-shear dispersion of silica aerogel and wetting and coating of polydimethylsiloxane; the upper limit of 265℃ can suppress high-temperature degradation of the membrane-source recycled polyester due to its low molecular weight and complex thermal history, and avoid further deterioration of melt strength; if the temperature is too low, the melt viscosity will increase and the dispersion shear will intensify, causing the silica aerogel skeleton to break; if the temperature is too high, it will intensify thermal degradation, limit the subsequent chain extension and thickening effect, and reduce spinning stability; And / or, the molecular weight of the polydimethylsiloxane is 6000 g / mol-10000 g / mol, and the addition amount is 0.5 wt%-1 wt% of the first membrane source recycled polyester; limiting this molecular weight and addition amount can ensure that the polydimethylsiloxane forms a continuous and stable interfacial coating layer in the melt; when the molecular weight is lower than 6000 g / mol, the polydimethylsiloxane chain is short, the volatility is high, it is easily lost in the high temperature molten state and has poor film-forming properties, and cannot effectively isolate the polyester melt from the gas condensation. When the molecular weight of the aerogel exceeds 10,000 g / mol, its viscosity increases significantly due to the wetting and clogging of the pores. This leads to a decrease in compatibility with low-viscosity carrier resins, and excessive entanglement can cause uncontrolled melt viscosity during spinning. When the addition amount is less than 0.5 wt%, the aerogel surface is not fully coated, and the thermal insulation skeleton is not adequately protected. When the addition amount is greater than 1 wt%, excessive siloxane migrates and accumulates on the fiber surface, which can easily cause melt sticking to the rollers and filament sticking. At the same time, it makes the surface friction coefficient of the fiber too low, reducing the subsequent cohesion and spinnability. And / or, the silica aerogel has a particle size of 50nm-100nm and a specific surface area of 500m². 2 / g-800m 2 / g, porosity >90%, the addition amount is 8.7wt%-17.7wt% of the first membrane source recycled polyester; this addition amount is a balance between the melt load limit of the low viscosity membrane source recycled polyester and the thermal insulation function requirements. The lower limit of 8.7wt% can ensure the formation of a continuous and effective porous thermal insulation network inside the fiber, significantly improving the thermal insulation rate of the floc to achieve high-value applications. Below this content, the thermal insulation contribution is insufficient and it is difficult to achieve the functional effect. The upper limit of 17.7wt% is limited by the background melt strength of the first membrane source recycled polyester. If the addition amount is too high, it will greatly increase the melt viscosity and cohesive energy, causing difficulties in twin-screw dispersion, aerogel agglomeration, and triggering melt breakage and increased breakage rate in spinning. At the same time, a high proportion of rigid particles will significantly degrade the mechanical properties of the fiber. This addition range can ensure the integrity of the three-dimensional skeleton structure of silica aerogel during spinning, and maintain the spinnability and fiber forming continuity of the low viscosity recycled polyester system.
[0009] In one embodiment of the present invention, in S1, the shear rate of the twin screw is 500 s. -1 -800s -1The mixing speed was 30-80 rpm, and the mixing time was 5-15 min. The above shear rate, speed, and time range were set to balance the uniform dispersion of silica aerogel and the preservation of the skeleton structure. The shear rate was a medium-low intensity shear, which can overcome the agglomeration force of aerogel particles and achieve full wetting and coating of polydimethylsiloxane on the aerogel surface. It is also much lower than the high shear conditions of traditional functional masterbatch preparation, which can avoid the breakage and pore collapse of the three-dimensional porous skeleton of silica aerogel under strong shear. The speed was matched with this shear range to further suppress the cumulative shear effect. If the mixing time is less than 5 min, the aerogel will be unevenly dispersed in the low viscosity melt and the polydimethylsiloxane coating will be incomplete. If it exceeds 15 min, it will increase the risk of cumulative shear heat and thermo-oxidative degradation, which will not only destroy the integrity of the aerogel skeleton, but also cause the low molecular weight membrane source polyester to further deteriorate the melt strength due to prolonged heating, affecting the stability of subsequent spinning.
[0010] In one embodiment of the present invention, in S2, the chain extender is glycidyl etheroxypropyl-isooctyl polysilsesquioxane, and the addition amount is 0.2wt%-0.9wt% of the pre-dispersed melt. This addition amount can achieve a balance between effective chain extension and thickening of low-viscosity membrane-source recycled polyester and spinning rheology. The lower limit of 0.2wt% can ensure that the epoxy groups of the chain extender react fully with the polyester end groups, raising the intrinsic viscosity to the spinnable range and compensating for insufficient melt strength caused by low molecular weight. Below this value, the degree of chain extension and branching is limited, and breakage and fuzzing problems are still likely to occur during spinning. The upper limit of 0.9wt% can avoid excessive branching or crosslinking that causes a sharp increase in melt viscosity or even gelation, preventing deterioration of spinning rheology and fiber mechanical properties. At the same time, the silicon-containing chain extender and polydimethylsiloxane have low surface energy, which can play an internal lubricating role and further improve the dispersibility of silica aerogel in the melt.
[0011] In one embodiment of the present invention, in S2, the reaction temperature is 260℃-270℃, the vacuum degree is ≤500Pa, and the time is 5min-10min. These reaction conditions are set to ensure the chain extension and thickening efficiency and melt quality. The temperature is slightly higher than the melt blending temperature of S1, which can provide sufficient reaction activation energy for the epoxy groups of glycidyl etheroxypropyl-isooctyl polysilsesquioxane and the end groups of low molecular weight polyester, and can also avoid excessively high temperature from aggravating the thermal degradation of the membrane-source recycled polyester. The vacuum degree ≤500Pa can remove reaction by-products in time, promote the positive shift of the chain extension reaction equilibrium, and suppress bubble entrainment in the melt, ensuring the compactness of subsequent spinning. The reaction time is matched with the amount of chain extender added. If the time is less than 5min, the branching chain extension will be insufficient and the intrinsic viscosity will not be improved. If the time exceeds 10min, the heat accumulation effect will be significant, which can easily lead to excessive crosslinking or melt color deterioration, thereby affecting the spinning stability.
[0012] In one embodiment of the present invention, in S3, the intrinsic viscosity of the second membrane-source recycled polyester is 0.57 dL / g-0.62 dL / g, and its chemical structure is polyethylene terephthalate. This intrinsic viscosity range can take into account both the high recycling ratio of the membrane-source recycled polyester and the melt strength required by the spinning main melt. As the spinning main melt flow, it can provide sufficient molecular chain entanglement density to achieve the bearing and coating of the side-fed low-viscosity modified melt, and improve the overall strength and fiber formation stability of the composite melt through interfacial topological entanglement. When the viscosity is lower than 0.57 dL / g, the strength of the main melt is insufficient, making it difficult to suppress the viscosity fluctuations caused by the mixing of a high proportion of aerogel modified melt. The spinning process is prone to problems such as melt breakage, breakage, and difficulty in winding. When the viscosity is higher than 0.62 dL / g, the viscosity difference between the main melt and the low-viscosity modified component is too large, which will increase the difficulty of homogenization of the side-fed blending interface, easily produce microphase separation, and thus affect the fiber forming stability. And / or, the temperature of the molten second membrane-source recycled polyester is 275℃-285℃; this temperature range can ensure the melt quality and thermal stability of the high-viscosity membrane-source recycled polyester as the spinning body; the lower limit of 275℃ can ensure that the membrane-source polyester is fully plasticized, so that the melt viscosity is reduced to a suitable range, which facilitates the rapid homogenization and mixing of the side-fed modified melt, and avoids phase separation caused by local viscosity abrupt change; the upper limit of 285℃ can suppress the high-temperature degradation of the membrane-source polyester due to the low molecular weight background and thermal history accumulation, and prevent the deterioration of melt strength and color; if the temperature is too low, the viscosity of the main melt will be too high, and the interfacial entanglement with the low-viscosity modified component will be insufficient, and melt fracture will easily occur during spinning; if the temperature is too high, it will aggravate thermal degradation and cause the molecular chain to break more rapidly, thereby reducing the stability of filamentation and the mechanical properties of the fiber.
[0013] In one embodiment of the present invention, in S3, the mass ratio of the second membrane-source recycled polyester to the modified melt is (75-85):(15-25). This ratio is used to balance the functionalization requirements of the fiber and the stability of the spinning process. The lower limit of the modified melt proportion of 15% can ensure the effective content of silica aerogel in the fiber, and achieve a significant heat preservation effect in combination with the hollow cross section. If the proportion is lower than this, the functional contribution of aerogel is insufficient, making it difficult to achieve high-value applications. The upper limit of 25% is limited by the melt carrying capacity of the low-viscosity modified melt (the viscosity is still lower than that of the main resin after chain extension). If the proportion is too high, it will significantly reduce the overall strength of the composite melt, which will easily cause the spinning melt to break, break, and be difficult to wind. At the same time, the introduction of a high proportion of aerogel will aggravate the melt viscosity fluctuation and deteriorate the spinnability. The proportion of the second membrane-source recycled polyester of 75%-85% can maintain sufficient molecular chain entanglement density, effectively cover and anchor the low-viscosity modified component, and ensure the continuity of filamentation and the mechanical properties of the fiber.
[0014] In one embodiment of the present invention, in S3, the specific steps of the spinning are as follows: melt spinning is performed using a hollow spinneret, followed by ring blowing cooling, oiling, stretching and winding in sequence.
[0015] In one embodiment of the present invention, the melt spinning temperature is 270℃-280℃, and the speed is 800m / min-1500m / min. This process can balance the plasticization quality of the composite melt and the integrity of the silica aerogel skeleton. The lower limit of 270℃ ensures that the composite melt after side feeding and homogenization is fully plasticized and has a moderate viscosity, allowing it to be smoothly extruded through a hollow spinneret. Below this temperature, the high proportion of aerogel melt will have insufficient fluidity, uneven extrusion expansion, and difficulty in stably forming a hollow cross section. The upper limit of 280℃ can prevent the main resin from entering the critical range of thermal degradation and inhibit the regeneration of the membrane source. Ester molecular chain breakage and chain extension branching structure dissociation; spinning speed is in the medium-low forming range, with an upper limit of 1500m / min to control the axial tensile stress of the filament, preventing strong shear from causing aerogel skeleton breakage and low viscosity system melt fracture; the lower limit of 800m / min can provide sufficient spinneret stretching action to ensure stable forming of hollow cross section and maintain reasonable production efficiency; excessive spinning speed will exceed the melt strength tolerance range of low viscosity recycled polyester system, leading to an increase in breakage rate; excessive speed will easily cause the filament to over-cool, making it unable to match the subsequent stretching ratio, affecting fiber structure densification and mechanical properties; And / or, the annular cooling device is located below the spinneret and is divided into an initial cooling zone and a subsequent cooling zone along the direction of the filament bundle; the air temperature in the initial cooling zone is 18℃-22℃, and the air velocity is 0.8m / s-1.2m / s; the air temperature in the subsequent cooling zone is 25℃-30℃, and the air velocity is 0.4m / s-0.6m / s; these staged cooling parameters are specifically designed to adapt to low melt strength recycled polyester systems and protect the silica aerogel skeleton structure, with the initial cooling zone being fast. Rapid curing of the filament surface increases melt viscosity, inhibits hollow section collapse, and reduces axial shear damage to the aerogel during subsequent stretching. Excessive air temperature or low air velocity can lead to curing lag and aerogel skeleton breakage. The subsequent stage uses gentle cooling to complete the overall curing of the filament, avoiding excessive temperature difference between the skin and core, internal stress concentration, and fiber cracking caused by sudden cooling. Excessive air velocity or low temperature can easily cause filament vibration, breakage, and hollow structure distortion. The two-stage cooling works together to ensure fiber forming stability and aerogel skeleton integrity. And / or, the stretching temperature is 100℃-130℃, with a multiple of 2.5-3.5 times; this temperature and multiple range is specifically designed to adapt to low-viscosity film-source recycled polyester systems and preserve the functional framework of silica aerogel; the lower limit of 100℃ is higher than the glass transition temperature of recycled polyester, which allows molecular chain segments to have the ability to move to achieve oriented crystallization, while avoiding a sharp increase in tensile stress due to excessively low temperature, which could cause the aerogel framework to break and the hollow section to collapse; the upper limit of 130℃ is lower than the dangerous zone of thermal bonding of recycled polyester, which can prevent the fibers from sticking on the hot roller. The process involves connecting and binding fibers, while simultaneously inhibiting excessive relaxation of molecular chains to ensure the stability of the oriented structure. A lower limit of 2.5 times ensures sufficient orientation and crystallization of molecular chains, giving the fiber the necessary breaking strength and stabilizing the hollow cross section. Too low a multiple will lead to a loose fiber structure and insufficient mechanical and thermal insulation properties. An upper limit of 3.5 times is limited by the melt strength after chain extension and the interfacial bearing capacity limit of high-proportion aerogels. Too high a multiple will cause the axial tensile stress to exceed the interfacial bonding strength, leading to aerogel debonding, skeleton breakage or pore collapse. It also easily causes flattening of the hollow structure and a significant increase in the breakage rate.
[0016] A second objective of this invention is to provide a polyester-based silica aerogel fiber prepared by the method described above.
[0017] In one embodiment of the present invention, the polyester-based silica aerogel fiber has a fineness of 3dtex-10dtex and a hollowness of 15%-25%.
[0018] The technical solution of the present invention has the following advantages compared with the prior art: (1) The preparation method of the present invention uses low intrinsic viscosity membrane source recycled polyester as aerogel carrier. In its molten state, it forms a flexible coating layer on the surface of silica aerogel by means of the interfacial wetting characteristics of polydimethylsiloxane, so that the surface of aerogel is coated by polydimethylsiloxane, which isolates the polyester melt from the aerogel pores and prevents pore blockage. Then, a chain extender containing siloxane is used to extend the low viscosity component in situ to increase the viscosity and improve the melt strength. Finally, the modified low viscosity component is fed laterally into the high intrinsic viscosity membrane source recycled polyester melt. The molecular chain topological entanglement further improves the melt strength of the filament and improves the filament stability. This process can avoid the damage to the aerogel skeleton caused by secondary heating and strong shear in the traditional masterbatch spinning process.
[0019] (2) In the preparation method of the present invention, during the spinning process, the polydimethylsiloxane coated on the surface of silica aerogel migrates to the fiber surface driven by interfacial energy. At the same time, the low viscosity modified melt fed from the side tends to be distributed in the skin region in the composite melt flow field. The two work together to enrich the silica aerogel on the fiber surface. Combined with the hollow cross section design to form a gradient heat insulation structure, the porous skeleton structure of silica aerogel can be completely preserved during the spinning process, effectively improving the melt strength and spinnability of low-value membrane source recycled polyester, realizing its high-value utilization, and finally obtaining polyester-based silica aerogel fiber with excellent mechanical strength and high-efficiency heat preservation function. Detailed Implementation
[0020] The present invention will be further described below with reference to specific embodiments, so that those skilled in the art can better understand and implement the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. It should be understood that the specific embodiments are only used to explain the present invention, but the embodiments are not intended to limit the present invention.
[0021] In this invention, unless otherwise stated, the technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0022] In this invention, unless otherwise stated, the term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0023] In this invention, unless otherwise specified, the experimental methods used in the embodiments of this invention are conventional methods, and the materials and reagents used are commercially available unless otherwise specified.
[0024] In this invention, unless otherwise stated, the recycled polyester used in the embodiments of this invention needs to be pre-crushed and ground to a powder size of 40 mesh before use.
[0025] In this invention, unless otherwise stated, the recycled polyester used in the embodiments of this invention is commercially available white PET foam, purchased from Yichang Shengteng New Material Co., Ltd., with a chemical structure of polyethylene terephthalate. Based on the differentiated requirements of the process of this invention for the viscosity of raw materials, the commercially available white PET foam is directly subjected to strict intrinsic viscosity testing and grading screening. Moreover, the raw material grading screening method and key indicators can be directly reproduced by those skilled in the art through conventional testing methods (such as viscometer titration to measure intrinsic viscosity).
[0026] In this invention, unless otherwise stated, the polydimethylsiloxane used in the embodiments of this invention has a molecular weight of approximately 6000 g / mol and was purchased from Jiangxi Lanxing Xinghuo Organosilicon Co., Ltd.
[0027] In this invention, unless otherwise stated, the silica aerogel used in the embodiments of this invention has a particle size of approximately 75 nm and a specific surface area of 650 m². 2 / g, porosity 92%, purchased from Guangdong Elisheng Technology Co., Ltd.
[0028] In this invention, unless otherwise stated, the glycidyl etheroxypropyl-isooctyl polysilsesquioxane used in the embodiments of this invention was purchased from Guangzhou Yixin Technology Co., Ltd., with product number POSS 409.
[0029] In this invention, unless otherwise stated, in embodiments of this invention, the annular cooling device is disposed below the spinneret and is divided along the direction of the filament bundle travel into a primary cooling zone adjacent to the spinneret and a secondary cooling zone disposed downstream of the primary cooling zone.
[0030] Example 1
[0031] The polyester-based silica aerogel fiber and its preparation method in this embodiment specifically include the following steps: S1. Heat the membrane-derived recycled polyester with an intrinsic viscosity of 0.35 dL / g to a molten state, controlling the melt temperature at 255℃. First, add polydimethylsiloxane at a rate of 0.8 wt% of the membrane-derived recycled polyester. After it forms a continuous liquid film in the melt, add silica aerogel at a rate of 13 wt% of the membrane-derived recycled polyester. At a shear rate of 650 s⁻¹, [the process is repeated in the original text]. -1 The silica aerogel was stirred and mixed at low speed for 10 minutes under the shearing action of a twin-screw extruder at a speed of 55 rpm, so that the silica aerogel was fully dispersed and impregnated in the low-viscosity melt to obtain a pre-dispersed melt. S2. Add glycidyl etheroxypropyl-isooctyl polysilsesquioxane to the pre-dispersed melt at an amount of 0.5 wt%. React for 8 min at a temperature of 265℃ and a vacuum of 500 Pa to branch and extend the molecular chains of the membrane-source recycled polyester, thereby increasing the intrinsic viscosity to 0.50 dL / g and obtaining the modified melt. S3. The membrane-source recycled polyester with an intrinsic viscosity of 0.60 dL / g is heated and melted to obtain the main melt flow. The temperature is controlled at 280℃. The modified melt is injected into the main melt flow through a side feed port 18cm before the metering pump. The side feed ratio is 20% of the total mass. After being briefly homogenized by a static mixer with a residence time of 1min, it is then melt-spun through a hollow spinneret. The melt spinning temperature is controlled at 275℃ and the speed is 1150m / min. Staged ring blowing cooling is adopted. At a distance of 20cm from the spinneret, the air temperature in the first cooling zone is 20℃ and the air velocity is 1.0m / s, and the air temperature in the second cooling zone is 28℃ and the air velocity is 0.5m / s. After cooling, oil is applied sequentially, and the fibers are stretched at 115℃ at a multiple of 3. Finally, the fibers are wound to obtain polyester-based silica aerogel fibers.
[0032] Example 2
[0033] The polyester-based silica aerogel fiber and its preparation method in this embodiment specifically include the following steps: S1. Heat the membrane-derived recycled polyester with an intrinsic viscosity of 0.30 dL / g to a molten state, controlling the melt temperature at 245℃. First, add polydimethylsiloxane at a rate of 0.5 wt% of the membrane-derived recycled polyester. After it forms a continuous liquid film in the melt, add silica aerogel at a rate of 8.7 wt% of the membrane-derived recycled polyester. At a shear rate of 500 s⁻¹, [the process is repeated in the original text]. -1 Under the shearing action of a twin-screw extruder at a speed of 30 rpm, the mixture is stirred at low speed for 15 min to fully disperse and impregnate the silica aerogel in the low-viscosity melt, thus obtaining a pre-dispersed melt. S2. Add glycidyl etheroxypropyl-isooctyl polysilsesquioxane to the pre-dispersed melt at an amount of 0.2 wt%. React at 260 °C and 500 Pa for 10 min to branch and extend the molecular chains of the membrane-source recycled polyester, increasing the intrinsic viscosity to 0.45 dL / g, thus obtaining the modified melt. S3. The membrane-source recycled polyester with an intrinsic viscosity of 0.57 dL / g is heated and melted to obtain the main melt flow. The temperature is controlled at 275℃. The modified melt is injected into the main melt flow through a side feed port 18cm before the metering pump. The side feed ratio is 15% of the total mass. After being briefly homogenized by a static mixer with a residence time of 1min, it is then melt-spun through a hollow spinneret. The melt spinning temperature is controlled at 270℃ and the speed is 800m / min. Staged ring blowing cooling is adopted. At a distance of 20cm from the spinneret, the air temperature in the first cooling zone is 18℃ and the air velocity is 0.8m / s, and the air temperature in the second cooling zone is 25℃ and the air velocity is 0.4m / s. After cooling, oil is applied sequentially, and the fibers are stretched at 100℃ at a ratio of 2.5. Finally, the fibers are wound to obtain polyester-based silica aerogel fibers.
[0034] Example 3
[0035] The polyester-based silica aerogel fiber and its preparation method in this embodiment specifically include the following steps: S1. Heat the membrane-derived recycled polyester with an intrinsic viscosity of 0.40 dL / g to a molten state, controlling the melt temperature at 265℃. First, add polydimethylsiloxane at a rate of 1 wt% of the membrane-derived recycled polyester. After it forms a continuous liquid film in the melt, add silica aerogel at a rate of 17.7 wt% of the membrane-derived recycled polyester. At a shear rate of 800 s⁻¹, [the process is repeated in the original text]. -1 Under the shearing action of a twin-screw extruder at a speed of 80 rpm, the mixture is stirred at low speed for 5 minutes to fully disperse and impregnate the silica aerogel in the low-viscosity melt, thus obtaining a pre-dispersed melt. S2. Add glycidyl etheroxypropyl-isooctyl polysilsesquioxane to the pre-dispersed melt at an amount of 0.9 wt%. React for 5 min at a temperature of 270℃ and a vacuum of 500 Pa to branch and extend the molecular chains of the membrane-source recycled polyester, thereby increasing the intrinsic viscosity to 0.55 dL / g and obtaining the modified melt. S3. The membrane-source recycled polyester with an intrinsic viscosity of 0.62 dL / g is heated and melted to obtain the main melt flow. The temperature is controlled at 285℃. The modified melt is injected into the main melt flow through a side feed port 18 cm before the metering pump. The side feed ratio is 25% of the total mass. After being briefly homogenized by a static mixer with a residence time of 1 min, it is then melt-spun through a hollow spinneret. The melt spinning temperature is controlled at 280℃ and the speed is 1500 m / min. Staged ring blowing cooling is adopted. At a distance of 20 cm from the spinneret, the air temperature in the first cooling zone is 22℃ and the air velocity is 1.2 m / s, and the air temperature in the second cooling zone is 30℃ and the air velocity is 0.6 m / s. After cooling, oil is applied sequentially, and the fibers are stretched at 130℃ at a ratio of 3.5. Finally, the fibers are wound to obtain polyester-based silica aerogel fibers.
[0036] Comparative Example 1
[0037] The process is basically the same as in Example 1, except that the membrane-source recycled polyester with an intrinsic viscosity of 0.35 dL / g in S1 is replaced with a membrane-source recycled polyester with an intrinsic viscosity of 0.60 dL / g.
[0038] Comparative Example 2
[0039] The process is basically the same as in Example 1, except that the membrane-source recycled polyester with an intrinsic viscosity of 0.60 dL / g in S3 is replaced with a membrane-source recycled polyester with an intrinsic viscosity of 0.35 dL / g.
[0040] Comparative Example 3
[0041] The basic structure is the same as in Example 1, except that the polydimethylsiloxane in S1 is replaced with polyethylene glycol (purchased from Aladdin Biochemical Technology Co., Ltd., with a molecular weight of approximately 6000 g / mol).
[0042] Comparative Example 4
[0043] The basic structure is the same as in Example 1, except that polydimethylsiloxane is not used in S1.
[0044] Comparative Example 5
[0045] The process is basically the same as in Example 1, except that the silica aerogel in S1 is replaced with non-porous solid silica microspheres (purchased from Evonik Industries, catalog number OX 50, with a particle size of approximately 40 nm).
[0046] Comparative Example 6
[0047] The basic principle is the same as in Example 1, except that silica aerogel is not used in S1.
[0048] Comparative Example 7
[0049] The process is basically the same as in Example 1, except that glycidyl etheroxypropyl-isooctyl polysilsesquioxane in S2 is replaced with a polyepoxy chain extender (purchased from BASF, catalog number ADR 4468).
[0050] Comparative Example 8
[0051] It is basically the same as Example 1, except that the S2 operation is not performed.
[0052] Test Example 1
[0053] Performance tests were performed on the fibers prepared in the examples and comparative examples: (1) Fineness: Tested according to the standard of the yarn method in GB / T 14343-2008 Chemical Fiber Filament Linear Density Test Method; (2) Hollowness: Tested according to the standard of "FZ / T 50002-2013 Test Method for the Deformity of Chemical Fibers"; (3) Breaking strength: Tested in accordance with the standard of GB / T 14344-2008 Test method for tensile properties of chemical fiber filaments; (4) Thermal insulation rate: Tested in accordance with the standard of GB / T 35762-2017 Test method for heat transfer properties of textiles, plate method; Table 1 shows the final measured parameters: Table 1
[0054] As can be seen from Table 1, the polyester-based silica aerogel fiber of the embodiment has a full and uniform crimped structure, excellent compression resilience, and can maintain efficient and stable thermal insulation performance in both dry and wet environments. Its heat insulation effect is outstanding, and its overall performance is superior to that of the comparative examples.
[0055] Comparing Example 1 and Comparative Example 1, it can be seen that the fiber strength and heat insulation effect of Comparative Example 1 are significantly worse. This is because S1 uses high-viscosity membrane source polyester as a carrier, the melt viscosity is too high, the shearing effect during the dispersion process is too strong, which leads to the destruction of the porous skeleton of the aerogel and the collapse of the pores. At the same time, uneven dispersion and agglomeration are aggravated, which ultimately causes the fiber mechanical properties and heat insulation performance to decline simultaneously.
[0056] Comparing Example 1 and Comparative Example 2, it can be seen that Comparative Example 2 cannot be stably filamentized and does not have qualified fiber properties. This is because the main spinning resin is changed to a low-viscosity film-source polyester, the overall molecular chain entanglement of the composite melt is insufficient, the melt strength is too low, and it cannot withstand stress during spinning stretching and winding, making it difficult to form continuously.
[0057] Comparing Example 1 and Comparative Example 3, it can be seen that the fiber strength and thermal insulation rate of Comparative Example 3 are significantly reduced. This is because after replacing polydimethylsiloxane with polyethylene glycol, the interfacial compatibility is poor, and a continuous and effective coating layer cannot be formed on the aerogel surface. This easily causes aerogel agglomeration and pore blockage, and it is impossible to form a gradient thermal insulation structure enriched by the aerogel skin, ultimately leading to a significant deterioration in mechanical and thermal insulation properties.
[0058] Comparing Example 1 and Comparative Example 4, it can be seen that the fiber strength and thermal insulation performance of Comparative Example 4 decreased significantly. This is because without the use of polydimethylsiloxane, the aerogel lacks flexible interface protection, and the polyester melt directly invades and blocks the pores. At the same time, the inorganic-organic interface bonding deteriorates and stress concentration is obvious, which not only damages the thermal insulation structure but also reduces the mechanical properties of the fiber.
[0059] Comparing Example 1 and Comparative Example 5, it can be seen that the fiber strength of Comparative Example 5 is acceptable, but the heat preservation effect is significantly weaker. This is because solid nano-silica is used to replace porous aerogel, which lacks a three-dimensional nanoporous heat insulation network. Relying solely on particle filling cannot achieve low thermal conductivity and high-efficiency heat insulation, and its heat preservation ability is far inferior to that of the aerogel system.
[0060] Comparing Example 1 and Comparative Example 6, it can be seen that the fiber strength of Comparative Example 6 is slightly reduced and the thermal insulation performance is significantly reduced. This is because without the addition of aerogel, the fiber only relies on the hollow structure for thermal insulation, lacking the synergistic thermal insulation effect of the porous skeleton of aerogel, resulting in limited thermal insulation capacity and failing to achieve a high level of thermal insulation.
[0061] Comparing Example 1 and Comparative Example 7, it can be seen that the fiber strength and heat insulation effect of Comparative Example 7 are significantly worse. This is because after using a common chain extender, the interfacial compatibility with the siloxane coating layer is worse, the overall melt bonding force decreases, the enrichment effect of the aerogel skin layer is weakened, the hollow structure formation is worse, and ultimately both mechanical properties and thermal insulation performance are affected.
[0062] Comparing Example 1 and Comparative Example 8, it can be seen that Comparative Example 8 has poor fiber stability and cannot produce qualified fibers. This is because the chain extension and thickening step is omitted, the melt strength of the low viscosity component is insufficient, the overall strength of the composite melt is too low, and it cannot meet the requirements of spinning stretching and stable forming, resulting in poor production continuity.
[0063] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A method for preparing polyester-based silica aerogel fibers, characterized in that, Includes the following steps: S1. Under the shearing action of a twin-screw extruder, polydimethylsiloxane and silica aerogel are sequentially added to the molten first membrane-source recycled polyester and mixed evenly to obtain a pre-dispersed melt; the intrinsic viscosity of the first membrane-source recycled polyester is 0.30 dL / g-0.40 dL / g; the chemical structure of the first membrane-source recycled polyester is polyethylene terephthalate; the molecular weight of the polydimethylsiloxane is 6000 g / mol-10000 g / mol, and the addition amount is 0.5 wt%-1 wt% of the first membrane-source recycled polyester; the particle size of the silica aerogel is 50 nm-100 nm, and the specific surface area is 500 m² / g. 2 / g-800m 2 / g, porosity >90%, addition amount is 8.7wt%-17.7wt% of the first membrane source recycled polyester; S2. Add a chain extender to the pre-dispersed melt described in S1 and react to obtain a modified melt; the chain extender is glycidyl etheroxypropyl-isooctyl polysilsesquioxane, and the amount added is 0.2wt%-0.9wt% of the pre-dispersed melt; S3. Add the modified melt described in S2 to the molten second membrane source recycled polyester, homogenize it, and then spin it to obtain the polyester-based silica aerogel fiber; the intrinsic viscosity of the second membrane source recycled polyester is 0.57 dL / g-0.62 dL / g; the chemical structure of the second membrane source recycled polyester is polyethylene terephthalate.
2. The method for preparing polyester-based silica aerogel fibers according to claim 1, characterized in that, In S1, the temperature of the molten first membrane source recycled polyester is 245°C-265°C.
3. The method for preparing polyester-based silica aerogel fibers according to claim 1, characterized in that, In S1, the shear rate of the twin screw is 500 s. -1 -800s -1 The rotation speed is 30rpm-80rpm, and the time is 5min-15min.
4. The method for preparing polyester-based silica aerogel fibers according to claim 1, characterized in that, In S2, the reaction temperature is 260℃-270℃, the vacuum degree is ≤500Pa, and the time is 5min-10min.
5. The method for preparing polyester-based silica aerogel fibers according to claim 1, characterized in that, In S3, the temperature of the molten second membrane source recycled polyester is 275°C-285°C.
6. The method for preparing polyester-based silica aerogel fibers according to claim 1, characterized in that, In S3, the mass ratio of the second membrane source recycled polyester to the modified melt is (75-85):(15-25).
7. The method for preparing polyester-based silica aerogel fibers according to claim 1, characterized in that, In S3, the specific steps of the spinning process are as follows: melt spinning is performed using a hollow spinneret, followed by ring blowing cooling, oiling, stretching, and winding.
8. The method for preparing polyester-based silica aerogel fibers according to claim 7, characterized in that, The melt spinning temperature is 270℃-280℃, and the speed is 800m / min-1500m / min; And / or, the annular cooling device is located below the spinneret and is divided into a primary cooling zone and a secondary cooling zone along the direction of the filament bundle; the air temperature in the primary cooling zone is 18℃-22℃, and the air velocity is 0.8m / s-1.2m / s; the air temperature in the secondary cooling zone is 25℃-30℃, and the air velocity is 0.4m / s-0.6m / s; And / or, the stretching temperature is 100℃-130℃, and the stretching ratio is 2.5-3.5 times.
9. Polyester-based silica aerogel fibers prepared by the method of any one of claims 1-8.
Citation Information
Patent Citations
Preparation method of heat-insulating polyester nanofiber membrane
CN114635229A
Method for manufacturing thermal insulation fabric by using waste textiles
CN115198425A